Copolymer, piezoelectric material, piezoelectric film, and piezoelectric element
By copolymerizing with acrylonitrile using a copolymer containing a triazole framework, the problem of insufficient heat resistance of existing ferroelectric polymer piezoelectric materials is solved, high heat resistance and good piezoelectric characteristics are achieved, and the application temperature range is expanded.
Patent Information
- Application Number
- CN202380059644.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-07-05
- Publication Date
- 2025-03-28
AI Technical Summary
The heat resistance of existing ferroelectric polymer piezoelectric materials is insufficient, resulting in the loss of piezoelectric characteristics at high temperatures and the low glass transition temperature, which limits its application range.
A copolymer containing a triazole framework is used to copolymerize with acrylonitrile to form a piezoelectric material with high polarity and good heat resistance.
It achieves high heat resistance and good piezoelectric characteristics, and expands the temperature range of piezoelectric materials.
Smart Images

Figure CN119731224A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copolymer, a piezoelectric material, a piezoelectric film and a piezoelectric element.
[0002] This application claims priority based on Japanese Patent Application No. 2022-133097 filed in Japan on August 24, 2022, the contents of which are cited herein. Background Art
[0003] At present, the piezoelectric material forming the piezoelectric body of the piezoelectric element is mostly PZT (PbZrO3-PbTiO3 solid solution) which is a ceramic material. However, PZT has the defect that it is very brittle because it contains lead. Therefore, as a piezoelectric material, a material with low environmental load and rich flexibility is required.
[0004] As a piezoelectric material that meets such requirements, it is considered to use a polymer piezoelectric material. As a polymer piezoelectric material, there are ferroelectric polymers such as polyvinylidene fluoride (PVDF), vinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE)). However, the heat resistance of these ferroelectric polymers is insufficient. Therefore, when the piezoelectric body composed of existing ferroelectric polymers is raised to a high temperature, the piezoelectric characteristics will be lost, and the physical properties such as elastic modulus will also deteriorate. Therefore, the temperature range in which the piezoelectric element having a piezoelectric body composed of existing ferroelectric polymers can be used is narrow.
[0005] In addition, as a piezoelectric material, there is an amorphous polymer piezoelectric material that obtains piezoelectricity by polarizing and cooling at a temperature near the glass transition temperature. When the temperature of the amorphous polymer reaches near the glass transition temperature, the piezoelectric property disappears. Therefore, an amorphous polymer piezoelectric material with a high glass transition temperature and good heat resistance is required.
[0006] Examples of amorphous polymer piezoelectric materials having a high glass transition temperature include vinylidene cyanide-vinyl acetate copolymers (see, for example, Patent Document 1). However, vinylidene cyanide-vinyl acetate copolymers require the use of vinylidene cyanide as a raw material monomer, which is difficult to handle.
[0007] In addition, as the raw material monomer of the polymer piezoelectric material, it is conceivable to use acrylonitrile, which is easy to handle, instead of vinylidene cyanide. However, the glass transition temperature of the polymer using acrylonitrile as the raw material monomer is low. In addition, the piezoelectric properties of the polymer using acrylonitrile as the raw material monomer are also relatively low (for example, refer to non-patent document 1 and non-patent document 2).
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 1991 / 013922
[0011] Non-patent literature
[0012] Non-patent document 1: H. Ueda, S. Carr, Piezoelectricity in Polyacrylonitrile. Polym J 16, 661-667 (1984).
[0013] Non-patent document 2: H. von Berlepsch, W. Kunstler, Piezoelectricity of acrylonitrile / methylacrylate copolymer. Polymer Bulletin 19, 305-309 (1988). Summary of the invention
[0014] The technical problem that the invention is intended to solve
[0015] There has been a demand for a polymer piezoelectric material that can provide a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0016] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a copolymer that can be used as a piezoelectric material for obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0017] Another object of the present invention is to provide a piezoelectric material comprising the copolymer of the present invention and capable of obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0018] Another object of the present invention is to provide a piezoelectric film having high heat resistance and piezoelectric characteristics, which includes the copolymer of the present invention, and a piezoelectric element having high heat resistance and piezoelectric characteristics, which includes the piezoelectric film of the present invention.
[0019] Technical solutions to solve problems
[0020] In order to solve the above technical problems, the following technical solutions are provided. One embodiment of the present invention provides a copolymer having a structural unit containing a triazole skeleton and a structural unit represented by the following formula (2), wherein the structural unit containing a triazole skeleton is any one or more of the following general formulas (1-1) to (1-3).
[0021]
[0022] In the general formulas (1-1) to (1-3), R 1 ~R 6are any one selected from the group consisting of a hydrogen atom, a methyl group, a trifluoromethyl group, a nitrile group, a fluorine atom, a methoxy group, an ethyl group, an ethoxy group, a methoxymethyl group, a propyl group, an isopropyl group, a cyclopropyl group, a butyl group, an isobutyl group, a (trimethyl)methyl group, a (trimethyl)silyl group, a pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a cyclopentyl group, a hexyl group, a cyclohexyl group, a phenyl group, a tolyl group, a benzyl group, and a phenoxymethyl group, or R 1 ~R 6 Together with the triazole ring, they form a benzotriazole skeleton.
[0023] Effects of the Invention
[0024] The copolymer of the present invention has a structural unit comprising a triazole skeleton of any one or more of general formulae (1-1) to (1-3) and a structural unit represented by formula (2). Therefore, the copolymer of the present invention can be used as a piezoelectric material for obtaining a piezoelectric film having high heat resistance and piezoelectric properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The polymer of Example 3 1 H-NMR measurement chart.
[0026] Figure 2 yes Figure 1 A magnified view of a part of the image.
[0027] Figure 3 The polymer of Example 8 1 H-NMR measurement chart.
[0028] Figure 4 yes Figure 3 A magnified view of a part of the image. DETAILED DESCRIPTION
[0029] In order to solve the above-mentioned problems, the present inventors paid attention to the heat resistance of polymers using acrylonitrile as a raw material monomer and conducted intensive studies.
[0030] As a result, the inventors have found that it is sufficient to prepare a copolymer having a specific structural unit containing a triazole skeleton and a structural unit derived from acrylonitrile.
[0031] The compound with vinyl bonded to the nitrogen atom of the triazole skeleton has a high affinity with acrylonitrile. Therefore, the compound with vinyl bonded to the nitrogen atom of the triazole skeleton can form a copolymer with acrylonitrile. In addition, the compound with vinyl bonded to the nitrogen atom of the triazole skeleton is a five-membered ring aromatic compound with high polarity, and by copolymerizing it with acrylonitrile, a copolymer with good heat resistance compared with polyacrylonitrile is formed.
[0032] Specifically, the dipole moment of the compound containing a triazole skeleton is about 4.0 to 5.0 Debye, and the dipole moment of acrylonitrile is about 3.8 Debye. That is, the structural unit containing a triazole skeleton has a higher polarity than the structural unit derived from acrylonitrile. As a result, in the copolymer having a structural unit containing a triazole skeleton and a structural unit derived from acrylonitrile, the ordered structure that can be formed by the polar group (i.e., nitrile group) derived from acrylonitrile is disrupted by the structural unit containing a triazole skeleton with high polarity, and it is difficult to orient in a manner that cancels out the polarity. In addition, the copolymer has good heat resistance from the five-membered ring aromatic compound possessed by the structural unit containing a triazole skeleton. It is inferred from this that the copolymer having a structural unit containing a triazole skeleton and a structural unit derived from acrylonitrile becomes a piezoelectric material that can obtain a piezoelectric film with good heat resistance and piezoelectric properties.
[0033] In addition, a compound having a vinyl group bonded to a nitrogen atom of a triazole skeleton is smaller in size and has higher polarity than, for example, a compound having a six-membered ring skeleton or a triazine skeleton, and therefore can contain more structural units having a triazole skeleton having higher polarity when used as a piezoelectric material.
[0034] Consider using a compound having a skeleton similar to a triazole skeleton to replace the compound containing a triazole skeleton. Specifically, for example, consider using a compound having a five-membered ring containing a nitrogen atom in the same manner as triazole, that is, a compound containing an imidazole skeleton having 2 nitrogen atoms contained in the five-membered ring, a compound containing a skeleton having 4 nitrogen atoms contained in the five-membered ring; a compound containing a six-membered ring skeleton containing nitrogen, etc. However, in a copolymer having a structural unit containing an imidazole skeleton and a structural unit from acrylonitrile, due to the high alkalinity of the compound containing the imidazole skeleton, there is a defect of being easily decomposed. In addition, the polarity of the compound containing a skeleton having 4 nitrogen atoms contained in the five-membered ring and the compound containing a six-membered ring skeleton containing nitrogen is small. Therefore, the piezoelectric film containing a copolymer having a structural unit from these compounds instead of a structural unit containing a triazole skeleton cannot obtain good heat resistance and piezoelectric properties.
[0035] The present inventors produced a copolymer having a specific structural unit including a triazole skeleton and a structural unit derived from acrylonitrile and confirmed that the copolymer had good heat resistance and that a piezoelectric film using the copolymer as a piezoelectric material had good piezoelectric properties, thereby arriving at the present invention.
[0036] The present invention includes the following aspects.
[0037] [1] A copolymer comprising a structural unit containing a triazole skeleton and a structural unit represented by the following formula (2), wherein the structural unit containing a triazole skeleton is any one or more of the following general formulas (1-1) to (1-3).
[0038]
[0039] (In general formula (1-1) to general formula (1-3), R 1 ~R 6 are any one selected from the group consisting of a hydrogen atom, a methyl group, a trifluoromethyl group, a nitrile group, a fluorine atom, a methoxy group, an ethyl group, an ethoxy group, a methoxymethyl group, a propyl group, an isopropyl group, a cyclopropyl group, a butyl group, an isobutyl group, a (trimethyl)methyl group, a (trimethyl)silyl group, a pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a cyclopentyl group, a hexyl group, a cyclohexyl group, a phenyl group, a tolyl group, a benzyl group, and a phenoxymethyl group, or R 1 ~R 6 Together with the triazole ring, they form a benzotriazole skeleton.
[0040] [2] The copolymer according to [1], wherein in the general formulas (1-1) to (1-3), R 1 ~R 6 A hydrogen atom.
[0041] [3] The copolymer according to [1] or [2], wherein the content of the structural unit represented by the formula (2) is 20 to 80 mol%.
[0042] [4] A piezoelectric material comprising the copolymer described in [1] to [3].
[0043] [5] A piezoelectric film comprising the copolymer described in [1] to [3].
[0044] [6] A piezoelectric element comprising the piezoelectric film according to [5] and electrodes disposed on one surface and the other surface of the piezoelectric film, respectively.
[0045] Hereinafter, the copolymer, piezoelectric material, piezoelectric film, and piezoelectric element of the present invention will be described in detail.
[0046] [Copolymer]
[0047] The copolymer (polymer) of the present embodiment has a structural unit containing a triazole skeleton and a structural unit represented by formula (2).
[0048] The structural unit containing a triazole skeleton is a structural unit represented by any one or more of formula (1-1) to formula (1-3). Therefore, the structural unit containing a triazole skeleton possessed by the copolymer can be a structural unit selected from formula (1-1) to formula (1-3), or it can be two or three structural units selected from formula (1-1) to formula (1-3). The structural unit containing a triazole skeleton possessed by the copolymer uses a small number of raw materials and can be easily manufactured. Therefore, it is preferably a structural unit selected from formula (1-1) to formula (1-3). In addition, since it is a piezoelectric material for obtaining a piezoelectric film with good heat resistance and piezoelectric properties, the structural unit containing a triazole skeleton is preferably composed of only any one of formula (1-1) and (1-3), and more preferably only composed of formula (1-3).
[0049] In the structural unit containing a triazole skeleton possessed by the copolymer of this embodiment, R 1 ~R 6 are selected from any one of hydrogen atom, methyl, trifluoromethyl, nitrile, fluorine, methoxy, ethyl, ethoxy, methoxymethyl, propyl, isopropyl, cyclopropyl, butyl, isobutyl, (trimethyl)methyl, (trimethyl)silyl, pentyl, isopentyl, tert-pentyl, neopentyl, cyclopentyl, hexyl, cyclohexyl, phenyl, tolyl, benzyl, and phenoxymethyl. In the copolymer of the present embodiment, R of the structural unit containing the triazole skeleton 1 ~R 6 In addition, in the copolymer of the present embodiment, R 1 ~R 6 Since the above groups are present, the piezoelectric film can be used as a material for a piezoelectric film having excellent heat resistance and piezoelectric properties. 1 ~R 6 The volume is preferably small. This is because, in the structural unit containing the triazole skeleton, the volume ratio of the triazole ring that is beneficial to high polarity can be ensured. Specifically, R 1 ~R 6 It is preferably a hydrogen atom or a nitrile group, and more preferably a hydrogen atom.
[0050] In the structural unit containing the triazole skeleton, R 1 ~R 6 The R of the structural unit containing the triazole skeleton in the copolymer of this embodiment may form a benzotriazole skeleton together with the triazole ring. 1 ~R 6 When a benzotriazole skeleton is formed together with a triazole ring, the benzotriazole can be easily produced and can be used as a material for a piezoelectric film having excellent heat resistance and piezoelectric characteristics.
[0051] In the copolymer of the present embodiment, the arrangement order of the structural unit containing the triazole skeleton as a repeating unit and the structural unit represented by formula (2) is not particularly limited. In addition, in the copolymer of the present embodiment, the number of the structural unit containing the triazole skeleton and the number of the structural unit represented by formula (2) may be the same or different. Therefore, the copolymer of the present embodiment may be an alternating arrangement portion in which the structural unit containing the triazole skeleton and the structural unit represented by formula (2) are alternately arranged, a random arrangement portion in which the structural unit containing the triazole skeleton and the structural unit represented by formula (2) are arranged in a disordered manner, and a block arrangement portion having a continuous arrangement portion of the structural unit containing the triazole skeleton and the structural unit represented by formula (2) The polymer is distributed according to an arbitrary proportion. In the copolymer of the present embodiment, in order to make it difficult for the nitrile groups contained in the structural unit represented by formula (2) to be oriented in a manner that cancels out polarity, it becomes a copolymer that can be used as a piezoelectric material with good heat resistance and piezoelectric properties, and preferably includes an alternating arrangement portion.
[0052] In the copolymer of the present embodiment, the content of the structural unit comprising a triazole skeleton is preferably 20 to 80 mol%, more preferably 20 to 70 mol%, and further preferably 30 to 70 mol%. When the content of the structural unit comprising a triazole skeleton is 20 mol% or more, a copolymer with better heat resistance is obtained. In addition, when the content of the structural unit comprising a triazole skeleton is less than 80 mol%, it is possible to prevent the piezoelectric film comprising the copolymer from becoming hard and brittle due to excessive content of the structural unit comprising the triazole skeleton. In addition, when the content of the structural unit comprising a triazole skeleton is less than 80 mol%, it is possible to suppress the moisture absorption of the structural unit comprising the triazole skeleton and cause the insulation resistance of the copolymer to decrease.
[0053] In the copolymer of the present embodiment, the content of the structural unit represented by formula (2) is preferably 20 to 80 mol%, more preferably 30 to 80 mol%, and further preferably 30 to 70 mol%. When the content of the structural unit represented by formula (2) is 20 mol% or more, a copolymer having high insulation resistance and capable of forming a soft piezoelectric film is obtained. In addition, when the content of the structural unit represented by formula (2) is 80 mol% or less, it is easy to ensure the content of the structural unit comprising the triazole skeleton. As a result, the nitrile groups contained in the structural unit represented by formula (2) are difficult to be oriented in a manner that offsets each other's polarity, and a copolymer of a piezoelectric film having better heat resistance and piezoelectric properties can be formed.
[0054] The copolymer of this embodiment may contain one or more other structural units other than the structural unit containing a triazole skeleton and the structural unit represented by formula (2) as required. Examples of the other structural units include structural units derived from known monomers or oligomers having a polymerizable unsaturated bond.
[0055] Among the structural units contained in the copolymer of this embodiment, the total content of the structural units containing a triazole skeleton and the structural units represented by formula (2) is preferably 50% by mass or more, more preferably 80% by mass or more, and may be 90% by mass or more, or may consist only of the structural units containing a triazole skeleton and the structural units represented by formula (2).
[0056] The weight average molecular weight (Mw) of the copolymer of the present embodiment is preferably 10,000 to 1,000,000. When the weight average molecular weight (Mw) of the copolymer is 10,000 or more, the film-forming property is good, and it is easy to manufacture a piezoelectric film including the copolymer of the present embodiment. When the weight average molecular weight (Mw) of the copolymer is 1,000,000 or less, it can be easily dissolved in a solvent, and a piezoelectric film can be easily manufactured using a coating liquid dissolved in a solvent.
[0057] "Method for producing copolymer"
[0058] The copolymer of the present embodiment can be produced, for example, by using a raw material monomer including a compound serving as a source of a structural unit including a triazole skeleton and acrylonitrile and a polymerization initiator such as azobisbutyronitrile and performing radical copolymerization according to a known method.
[0059] The polymerization conditions such as reaction temperature and reaction time when producing the copolymer of the present embodiment can be appropriately determined according to the composition of the raw material monomers and the like.
[0060] The compound that is the source of the structural unit containing a triazole skeleton is a compound in which the triazole skeleton and the atoms bonded to the carbon atoms of the triazole skeleton are the same as those of the structural unit containing a triazole skeleton, and a vinyl group is bonded to the nitrogen atom of the triazole skeleton.
[0061] Examples of the compound that is the source of the structural unit represented by formula (1-3) include 1-vinyl-1H-1,2,3-triazole, 1-vinyl-1H-1,2,3-triazole-4-methyl, 1-vinyl-1H-1,2,3-triazole-4-ethyl, 1-vinyl-1H-1,2,3-triazole-4-phenyl, 1-vinyl-1H-1,2,3-triazole-4-benzyl, 1-vinyl-1H-1,2,3-triazole-4-carbonitrile, and 1-vinyl-1H-1,2,3-triazole-4-trifluoromethyl.
[0062] Examples of the compound that is a source of the structural unit represented by the formula (1-2) include 1-vinyl-1H-1,2,4-triazole, 1-vinyl-1H-1,2,4-triazole-3-carbonitrile, and 1-vinyl-1H-1,2,4-triazole-3-trifluoromethyl.
[0063] Examples of the compound that is the source of the structural unit represented by formula (1-3) include 4-vinyl-4H-1,2,4-triazole, etc. The source can be appropriately determined according to the structure of the copolymer of the present embodiment as the target product.
[0064] "Piezoelectric Materials"
[0065] The piezoelectric material of the present embodiment includes the copolymer of the present embodiment. The copolymer of the present embodiment contained in the piezoelectric material of the present embodiment may be only one, or may be more than two. In addition, the piezoelectric material of the present embodiment may include one or more known polymers other than the copolymer of the present embodiment together with the copolymer of the present embodiment as needed.
[0066] "Piezoelectric film"
[0067] The piezoelectric film of this embodiment includes the copolymer of this embodiment.
[0068] The piezoelectric film of the present embodiment can be manufactured, for example, by the method shown below. The piezoelectric material of the present embodiment including the copolymer of the present embodiment is dissolved in a solvent to prepare a coating liquid. As the solvent, a well-known solvent such as N,N-dimethylformamide can be used. Then, the coating liquid is applied to a peelable substrate at a specified thickness to form a coating film. As the substrate, a well-known film such as a resin film can be used. As a coating method of the coating liquid, a well-known method can be used according to the coating thickness, the viscosity of the coating liquid, etc. Then, the coating film is dried to remove the solvent in the coating film to obtain a piezoelectric material sheet. The piezoelectric material sheet can be stretched as needed.
[0069] Then, the piezoelectric material sheet is peeled off from the substrate, and electrodes made of a known conductive material such as aluminum are respectively provided on one side and the other side of the piezoelectric material sheet. Next, a voltage is applied to the piezoelectric material sheet at a temperature near the glass transition temperature of the piezoelectric material forming the piezoelectric material sheet through the electrodes provided on both sides. Then, the piezoelectric material sheet is cooled while the voltage is applied. Thus, piezoelectricity is obtained. Through the above steps, a sheet-shaped piezoelectric film can be obtained.
[0070] The electrode for obtaining piezoelectricity may be directly used as a member for forming a piezoelectric element, or may be removed.
[0071] "Piezoelectric element"
[0072] The piezoelectric element of the present embodiment has the piezoelectric film of the present embodiment and electrodes respectively arranged on one side and the other side of the piezoelectric film. Specifically, a piezoelectric element having a sheet-shaped piezoelectric film and electrodes respectively arranged on one side and the other side of the piezoelectric film can be cited. As the material of the electrode, a known conductive material such as aluminum can be used.
[0073] The piezoelectric element of the present embodiment can be manufactured by, for example, providing electrodes on one surface and the other surface of a piezoelectric film by a known method such as a vapor deposition method.
[0074] The copolymer of the present embodiment has a structural unit including a triazole skeleton and a structural unit represented by formula (2). Therefore, the copolymer of the present embodiment can be used as a piezoelectric material for obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0075] Furthermore, since the piezoelectric material of the present embodiment includes the copolymer of the present embodiment, a piezoelectric film having high heat resistance and piezoelectric characteristics can be obtained.
[0076] In addition, the piezoelectric film of the present embodiment includes the copolymer of the present embodiment. Therefore, the piezoelectric film of the present embodiment and the piezoelectric element of the present embodiment including the piezoelectric film of the present embodiment are excellent in heat resistance and piezoelectric characteristics.
[0077] Although the embodiments of the present invention have been described in detail above, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution and other changes of the configuration may be made without departing from the gist of the present invention.
[0078] Example
[0079] "Example 1"
[0080] In a 100 ml Schlenk flask, 0.4 g (4 mmol) of 1-vinyl-1H-1,2,3-triazole represented by the following general formula (11) and 1 ml (16 mmol) of acrylonitrile were mixed, 10 mg (0.06 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.9 g of the polymer of Example 1. The yield was 72%.
[0081]
[0082] (In general formula (11), R 1 , R 2 is a hydrogen atom.)
[0083] The polymer of Example 1 was subjected to nuclear magnetic resonance (NMR) analysis using a NMR device (trade name: JNM-ECA500, manufactured by JEOL Ltd.) and dimethyl sulfoxide d6 (DMSO-d6) as a solvent. 1 The molecular structure was determined by H-NMR.
[0084] As a result, it was confirmed that the polymer of Example 1 had a structural unit represented by the general formula (1-1) (R 1 , R2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0085] In addition, according to Example 1 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 1 was 83 mol%.
[0086] "Example 2"
[0087] In a 100 ml Schlenk tube, 1.0 g (10 mmol) of 1-vinyl-1H-1,2,3-triazole and 1.0 ml (16 mmol) of acrylonitrile were mixed, and 18.7 mg (0.11 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was put into 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 1.5 g of the polymer of Example 2. The yield was 84%.
[0088] The polymer of Example 2 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that, like the polymer of Example 1, the polymer of Example 2 has a structural unit represented by the general formula (1-1) (R in the general formula (1-1) 1 , R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0089] In addition, according to Example 2 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 2 was 66 mol%.
[0090] "Example 3"
[0091] In a 100 ml Schlenk tube, 0.8 g (8 mmol) of 1-vinyl-1H-1,2,3-triazole and 0.5 ml (8 mmol) of acrylonitrile were mixed, and 9.5 mg (0.06 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.8 g of the polymer of Example 3. The yield was 77%.
[0092] The polymer of Example 3 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination. Figure 1 The polymer of Example 3 1 H-NMR measurement chart. Figure 2 yes Figure 1In addition, for the polymer of Example 3, use 1 The molecular structure was determined by H-NMR measurement. The results confirmed that, like the polymer of Example 1, the polymer of Example 3 has a structural unit represented by the general formula (1-1) (R in the general formula (1-1) 1 , R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0093] In addition, according to Example 3 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 3 was 50 mol%.
[0094] "Example 4"
[0095] In a 100 ml Schlenk tube, 0.8 g (8 mmol) of 1-vinyl-1H-1,2,3-triazole and 0.3 ml (4 mmol) of acrylonitrile were mixed, and 7.8 mg (0.05 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.6 g of the polymer of Example 4. The yield was 66%.
[0096] The polymer of Example 4 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that, like the polymer of Example 1, the polymer of Example 4 has a structural unit represented by the general formula (1-1) (R 1 , R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0097] In addition, according to Example 4 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 4 was 37 mol%.
[0098] "Example 5"
[0099] In a 100 ml Schlenk tube, 0.8 g (8 mmol) of 1-vinyl-1H-1,2,3-triazole and 0.1 ml (2 mmol) of acrylonitrile were mixed, and 6.9 mg (0.04 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.5 g of the polymer of Example 5. The yield was 58%.
[0100] The polymer of Example 5 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that, like the polymer of Example 1, the polymer of Example 5 has a structural unit represented by the general formula (1-1) (R in the general formula (1-1) 1 , R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0101] In addition, according to Example 5 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 5 was 19 mol%.
[0102] "Example 6"
[0103] In a 100 ml Schlenk tube, 0.2 g (2 mmol) of 1-vinyl-1H-1,2,4-triazole represented by the following general formula (12) and 0.5 ml (8 mmol) of acrylonitrile were mixed, 4.9 mg (0.03 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.5 g of the polymer of Example 6. The yield was 87%.
[0104]
[0105] (In general formula (12), R 3 , R 4 is a hydrogen atom.)
[0106] The polymer of Example 6 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Example 6 has a structural unit represented by the general formula (1-2) (R 3 , R 4 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0107] In addition, according to Example 6 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 6 was 80 mol%.
[0108] "Example 7"
[0109] In a 100 ml Schlenk tube, 0.5 g (5 mmol) of 1-vinyl-1H-1,2,4-triazole and 0.5 ml (8 mmol) of acrylonitrile were mixed, and 7.2 mg (0.04 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.7 g of the polymer of Example 7. The yield was 75%.
[0110] The polymer of Example 7 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Example 7 has a structural unit represented by the general formula (1-2) (R 3 , R 4 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0111] In addition, according to Example 7 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 7 was 61 mol%.
[0112] "Example 8"
[0113] In a 100 ml Schlenk tube, 0.8 g (8 mmol) of 1-vinyl-1H-1,2,4-triazole and 0.5 ml (8 mmol) of acrylonitrile were mixed, and 9.4 mg (0.06 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.8 g of the polymer of Example 8. The yield was 68%.
[0114] The polymer of Example 8 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. Figure 3 The polymer of Example 8 1 H-NMR measurement chart. Figure 4 Yes Figure 3 In addition, for the polymer of Example 8, use 1 The molecular structure was determined by H-NMR measurement. The results confirmed that, like the polymer of Example 6, the polymer of Example 8 has a structural unit represented by the general formula (1-2) (R in the general formula (1-2) 3 , R 4 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0115] In addition, according to Example 8 1The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 8 was 50 mol%.
[0116] "Example 9"
[0117] In a 100 ml Schlenk tube, 0.8 g (8 mmol) of 1-vinyl-1H-1,2,4-triazole and 0.3 ml (4 mmol) of acrylonitrile were mixed, and 7.8 mg (0.05 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.7 g of the polymer of Example 9. The yield was 75%.
[0118] The polymer of Example 9 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that, like the polymer of Example 6, the polymer of Example 9 has a structural unit represented by the general formula (1-2) (R in the general formula (1-2) 1 , R 2 is a hydrogen element. ) and a copolymer of a structural unit represented by formula (2).
[0119] In addition, according to Example 9 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 9 was 33 mol%.
[0120] "Example 10"
[0121] In a 100 ml Schlenk tube, 0.8 g (8 mmol) of 1-vinyl-1H-1,2,4-triazole and 0.1 ml (2 mmol) of acrylonitrile were mixed, and 6.9 mg (0.04 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.6 g of the polymer of Example 10. The yield was 69%.
[0122] The polymer of Example 10 was subjected to the same treatment as that of the polymer of Example 1. 1 The results of H-NMR measurement confirmed that, like the polymer of Example 6, the polymer of Example 10 has a structural unit represented by the general formula (1-2) (R 3 , R 4 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0123] In addition, according to Example 10 1The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 10 was 17 mol%.
[0124] "Comparative Example 1"
[0125] As the polymer in Comparative Example 1, polyacrylonitrile (trade name 181315, manufactured by Sigma-Aldrich Co.) was used.
[0126] "Comparative Example 2"
[0127] As the polymer of Comparative Example 2, poly(acrylonitrile-co-methyl acrylate) (trade name 517941, manufactured by Sigma-Aldrich Co., Ltd.) was used.
[0128] For the polymers of Examples 1 to 10 obtained as described above, R in the structural unit represented by the general formula (1-1) or the general formula (1-2) is 1 ~R 4 Table 1 shows the contents of the structural unit represented by the formula (2).
[0129] Table 1 shows the compound names of the polymers of Comparative Examples 1 and 2 and the contents of the structural unit represented by the formula (2) in the polymers.
[0130] [Table 1]
[0131]
[0132] The glass transition temperature (Tg) of the polymers of Examples 1 to 10 and Comparative Examples 1 and 2 was measured by the following method. The results are shown in Table 1.
[0133] (Measurement method of glass transition temperature (Tg))
[0134] Using a high-sensitivity differential scanning calorimeter (trade name, DSC6200, manufactured by Seiko Instruments Co., Ltd.), in a nitrogen atmosphere, the temperature was increased from 30°C to 200°C at a heating rate of 20°C per minute; the temperature was lowered from 200°C to 30°C at a cooling rate of 40°C per minute; and the temperature was increased from 30°C to 200°C at a heating rate of 20°C per minute. The inflection point during the second heating was determined as the glass transition temperature (Tg).
[0135] In addition, using the polymers of Examples 1 to 10, Comparative Examples 1 and 2 as piezoelectric materials, piezoelectric films were produced by the following method, and the piezoelectric constants d 33 The results are shown in Table 1.
[0136] (Manufacturing of piezoelectric film)
[0137] The piezoelectric material was dissolved in N,N-dimethylformamide as a solvent to prepare a 20 mass % polymer solution (coating solution). The obtained polymer solution was coated on a PET film (trade name, Lumirror (registered trademark), manufactured by Toray Industries, Ltd.) as a substrate in a manner to achieve a thickness of 50 μm after drying to form a coating film. Then, the coating film formed on the PET film was dried on a hot plate at 120°C for 6 hours to remove the solvent in the coating film, thereby obtaining a piezoelectric material sheet.
[0138] The obtained piezoelectric material sheet was peeled off from the PET film, and electrodes made of aluminum were respectively provided on one side and the other side of the piezoelectric material sheet by evaporation. Then, a high-voltage power supply device HARB-20R60 (manufactured by Matsusada Precision Inc.) was electrically connected to the electrodes of the piezoelectric material sheet, and maintained at 140°C for 15 minutes while applying an electric field of 100 MV / m. Then, the piezoelectric material sheet was slowly cooled to room temperature while maintaining the voltage applied, and polarization treatment was applied to obtain a sheet-like piezoelectric film.
[0139] (piezoelectric constant d 33 Determination method of
[0140] The piezoelectric film was mounted on the measuring device using a pin with a tip diameter of 1.5 mm as a sample fixture. 33 The measuring device used was PiezoMeter Systems PM200 from PIEZOTEST.
[0141] Piezoelectric constant d 33 The measured value of becomes a positive value or a negative value depending on the front and back sides of the piezoelectric film being measured. 33 The absolute value of the measured value is recorded.
[0142] As shown in Table 1, it can be confirmed that the polymers of Examples 1 to 10 have a higher glass transition temperature (Tg) and better heat resistance than the polymers of Comparative Examples 1 and 2. In addition, the piezoelectric constants d of the piezoelectric films of Examples 1 to 10 including the polymers of Examples 1 to 10 are higher than those of the piezoelectric films of Comparative Example 1 including the polymer of Comparative Example 1 and the piezoelectric films of Comparative Example 2 including the polymer of Comparative Example 2. 33 High, good piezoelectric properties.
[0143] In particular, the piezoelectric constant d of the piezoelectric films of the polymers of Examples 2 to 4 and 6 to 9 containing 20 to 80 mol % of the structural unit represented by formula (2) is33 High, good piezoelectric properties.
[0144] Industrial Applicability
[0145] The copolymer of the present invention can be used as a piezoelectric material for obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics.
Claims
1. A copolymer, wherein It has a structural unit including a triazole skeleton and a structural unit represented by the following formula (2), The structural unit containing a triazole skeleton is any one or more of the following general formulas (1-1) to (1-3), In the general formulas (1-1) to (1-3), R 1 ~R 6 are any one selected from the group consisting of a hydrogen atom, a methyl group, a trifluoromethyl group, a nitrile group, a fluorine atom, a methoxy group, an ethyl group, an ethoxy group, a methoxymethyl group, a propyl group, an isopropyl group, a cyclopropyl group, a butyl group, an isobutyl group, a (trimethyl)methyl group, a (trimethyl)silyl group, a pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a cyclopentyl group, a hexyl group, a cyclohexyl group, a phenyl group, a tolyl group, a benzyl group, and a phenoxymethyl group, or R 1 ~R 6 Together with the triazole ring, they form a benzotriazole skeleton.
2. The copolymer according to claim 1, wherein In the general formulas (1-1) to (1-3), R 1 ~R 6 A hydrogen atom.
3. The copolymer according to claim 1 or 2, wherein The content of the structural unit represented by the formula (2) is 20 to 80 mol%.
4. A piezoelectric material, in, The method comprises the copolymer described in claim 1 or claim 2.
5. A piezoelectric film, in, The method comprises the copolymer described in claim 1 or claim 2.
6. A piezoelectric element, wherein: A piezoelectric film according to claim 5 and electrodes respectively arranged on one surface and the other surface of the piezoelectric film.
Citation Information
Patent Citations
Settlement device and program
JP2022133097A
Vinylidene cyanide alternating copolymers
WO1991013922A1